Remote Sensing - Robert Massom (2007)
The Antarctic is unique, geographically, politically, and scientifically. It is the most remote, hostile, and dangerous continent, while at the same time it is the most pristine and least developed. Antarctica is the only major part of the Earth's landmass not directly governed by one nation, but under the control of a Treaty, with a multitude of acceding nations. The Encyclopedia of the Antarctic brings together large quantities of information on the wide variety of factors, issues and individuals influencing and relating to the Antarctic. No comparable book currently exists for this region. The Encyclopedia of the Antarctic discusses scientific activities and topics, but the 'human element' is also a significant part of the work, with entries on history, politics, legal issues, national research programs, scientific bases, historic huts, the United Nation's 'Question of Antarctica,' compliance with the Environmental Protocol, and tourism.